Assessment of resistance in psychotherapy: a systematic review - Koutsoukou-Argyraki, Asimina; Nikendei, Christoph; Friederich, Hans-Christoph; Spranz-Fogasy, Thomas; Montan, Inka (Psychoanalytic psychotherapy, 2025)
Examining the phenomenon of resistance in psychotherapy both promotes a profound understanding of mental health disorders and supports the psychotherapeutic treatment of patients. However, in-depth, targeted research on resistance is limited. The present review provides an overview of recent empirical research on resistance in psychotherapy. A systematic search on PubMed and PsycInfo for peer-reviewed studies on the phenomenon of resistance in psychotherapy published in the years 2000-2022 in English or German language was conducted. Twenty-two publications fulfilling the search criteria were found. Fifteen out of 19 clinical studies (79%) approach resistance using the concept of cognitive-behavioral therapy. Four out of 19 clinical studies (21%) investigate resistance in psychoanalytic or psychodynamic psychotherapy. The studies identified indicate a strong relationship between patient resistance and psychotherapeutic outcome. Furthermore, resistance appears to be related to aspects of the therapeutic relationship, such as therapist behavior, empathy of therapist, alliance and attachment. Empirical research on resistance in psychotherapy is an interesting, promising field of research. The present study shows a profound gap in empirical research on resistance in psychoanalytic and psychodynamic psychotherapy. A reliable and valid instrument to measure resistance based on psychoanalytic and psychodynamic definitions of resistance is needed.